The experience of internal (Domestic) migration among 30 Homeless Former Prisoners in Kuala Lumpur, Malaysia - Mohd Alif Jasni; Nazirah Hassan; Fauziah Ibrahim; Mohammad Rahim Kamaluddin (Faculty of Geography, Universitas Gadjah Mada, 2023)
The recurring return of homeless former prisoners to Chow Kit Road each time after being released from prison leads to various key questions. One of which: What is so interesting about Chow Kit Road that it has become a focal point for these homeless former prisoners? Their return to Chow Kit Road illustrates two big pictures, either they have no choice or they see Chow Kit Road as a suitable home for them. The repeated return of the homeless former prisoners indicated that they have developed a form of comfort and pleasure with the place. Hence, we conducted a qualitative study to understand the repetitive migration among the homeless former prisoners by interviewing 30 of them around Chow Kit Road. This study stopped the data collection process when the study's overall findings achieved data saturation. Atlas.ti software was utilised to perform the thematic coding process. This software provides a more systematic coding process. Several strategies were adopted in this study to increase the data's validity and reliability, triangulation, member check, peer review, long period in the field and audit trail. This study involved a larger qualitative sample by offering several diverse themes. Based on the findings, 11 sub-themes were grouped into 4 superordinate themes, namely social, economic and urban infrastructure, services, and personal offer factors. The social offer factor superordinate theme included sub-themes of familiarity with the environment, ease of getting drugs, and concentration of friends who are also former prisoners. Followed by the economic offer factor with the sub-theme of finding a job and easy ways to earn. The sub-themes of the urban infrastructure and service offer factor superordinate theme were access to transportation, plenty of food aid, and easy access to hospitals. While the sub-themes of the personal offer factor included wanting freedom, nowhere else to go, and bringing oneself away from family. These results added to the existing knowledge by considering migrations from chronic and marginal groups, i.e., the homeless former prisoners as study subjects.